a: \(B=xy\left(y^2-x\right)=1\cdot1\cdot\left(1^2-1\right)=0\)
b: \(B=xy\left(y^2-x\right)=-1\cdot\left(-1\right)\cdot\left[\left(-1\right)^2-\left(-1\right)\right]=1\cdot\left(1+1\right)=2\)
c: \(B=xy\left(y^2-x\right)=1\cdot\left(-1\right)\cdot\left[\left(-1\right)^2-1\right]=0\)
d: \(B=xy\left(y^2-x\right)=-1\cdot1\cdot\left[1^2-\left(-1\right)^2\right]=0\)
Bài 2:
\(B=xy^3-x^2y=xy\left(y^2-x\right)\)
a) \(x=1;y=1\Rightarrow B=1.1.\left(1^2-1\right)=0\)
b) \(x=-1;y=-1\Rightarrow B=\left(-1\right).\left(-1\right).\left[\left(-1\right)^2-\left(-1\right)\right]=2\)
c) \(x=1;y=-1\Rightarrow B=1.\left(-1\right).\left[\left(-1\right)^2-\left(-1\right)\right]=-2\)
d) \(x=-1;y=1\Rightarrow B=\left(-1\right).1.\left[1^2-\left(-1\right)\right]=-2\)